SIKLUS MENSTRUASI PADA MAHASISWI YANG MENGALAMI STRES DI STIKES YARSIS - Kamariyah, Nurul (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2013)
One characteristic of the young woman is menstruating. Menstruation is often accompanied by physical and mental disorders.  Knowing the characteristics of menstruation, menstrual disorders and their relationship to the activity, as well as efforts to reduce menstrual disorders.  The type of study is analytic with method of Cross Sectional Study, using questionnaires to 185 female students STIKes YARSIS in November 2009. The result 92.1% of respondents menarche at age 10-14. 90% of respondents have a longer period for 6-9 days, and 87.1% of respondents have a long cycle for 25-32 days. 81.7% is a more emotional feeling before menstruation. 89.2% of respondents experiencing pain in the lower abdomen during menstruation. Correlation levels before menstruation disorders with learning activities significancy worth 0.030 with 0.226 correlation value. 58.4% of respondents reducing premenstrual disorders with rest and 88.4% of respondents reduces menstrual complaints by lying. The more weight the menstrual complaints will increasingly affect the learning activities. Resting is considered the most effective measures to reduce noise both before and during menstruation